Solving university course scheduling problem using genetic algorithm and analyzing results with other algorithms - Alam, Md. Ashraful; Islam, Toushika; Joseph, Duke (BRAC University, 2016)
This thesis report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2015.